Dog diaries. Barry - Klimo, Kate (Klimo, Kate. Dog diaries, 2013)
Barry der Menschenretter, a Saint Bernard dog, reflects back on his life in the early 1800s at the Hospice of the Great Saint Bernard in the Swiss Alps, where he rescued some forty people from avalanches. Includes facts about the breed and the hospice.